N equals N plus one

Theorem: n=n+1

Proof:
(n+1)^2 = n^2 + 2*n + 1

Bring 2n+1 to the left:
(n+1)^2 – (2n+1) = n^2

Substract n(2n+1) from both sides and factoring, we have:
(n+1)^2 – (n+1)(2n+1) = n^2 – n(2n+1)

Adding 1/4(2n+1)^2 to both sides yields:
(n+1)^2 – (n+1)(2n+1) + 1/4(2n+1)^2 = n^2 – n(2n+1) + 1/4(2n+1)^2

This may be written:
[ (n+1) – 1/2(2n+1) ]^2 = [ n – 1/2(2n+1) ]^2

Taking the square roots of both sides:
(n+1) – 1/2(2n+1) = n – 1/2(2n+1)

Add 1/2(2n+1) to both sides:
n+1 = n


1 Star2 Stars3 Stars4 Stars5 Stars (1 оценок, среднее: 5.00 из 5)